Design of a novel heating device for infusion fluids in vitrectomy. (5th January 2018) - Mauro, Alessandro; Massarotti, Nicola; Salahudeen, M.; Cuomo, Francesca; Costagliola, Ciro; Ambrosone, Luigi; Romano, Mario R.
Highlights: A novel device for heating infusion fluids during vitrectomy surgery has been designed. The device allows to control the temperature of infusion fluids during vitrectomy. The temperature of infusion fluids during surgery is kept in mild hypothermia range. Post-operative complications due to low temperature can be reduced by using the device. Abstract: The aim of this paper is to present a novel device for heating the infusion fluids during vitrectomy surgery, to be used to avoid deep hypothermal conditions inside human eyes. The key aspect of the proposed device concerns its ability to control the temperature of infusion fluids and keep it within the mild hypothermia range, in order to reduce the post-operative complications due to low temperature. The operation of the heater has been analysed by means of a transient numerical model developed by the authors, taking into account the presence of the pipes inside which the fluids flow. Two main case studies have been considered in the present work, regarding the possible ways to operate the device that are based on preheating and no-preheating the pipes before the surgery. The numerical analysis carried out in the present study shows that the proposed device may be effectively used to obtain a favourable increase in the temperature of the infusion fluids and to avoid deep hypothermal conditions.